The Effectiveness of Social Play Therapy To Improve Social Skills And Abilities Of Children With Autism - MA Muazar Habibi (Jurnal Ilmiah POTENSIA, 2023)
In the last three years, many children in West Nusa Tenggara, especially in West Lombok Regency in Indonesia, have experienced a developmental disorder called autism. This can be seen from the rise in public attention to include this category of children in schools that hold inclusive classes, such as in Early Childhood Education-Elementary School Lenterahati Islamic Boarding School. The increase in autism is also evidenced by the emergence of various therapy centres for children with special needs, as well as the increasing number of participants enrolled and undergoing therapy. The initial survey results showed seven therapy centres and schools for such children in West Nusa Tenggara, where each centre comprises 25 to 30 students. This means that 375 children in this province suffer from this mental health condition. Therefore, this experience requires many people to think about alternative therapies to help increase positive behaviour and reduce negative symptoms of children with autism. Experts and observers know several alternative therapies, but most have not been fully implemented. This is due to the limited facilities available in therapy centres hence no data and facts show evidence for the effectiveness of applying them to improve the abilities of this category of children. Based on these needs, this research aims to apply therapy with a "social play" model to help improve the positive behaviour of children with autism and determine its contribution to achieving the goals. This therapy is selected as an alternative because it is cheap and can be carried out anywhere and by anyone. It also allows every parent or family with an autistic child to always provide therapy. This is quasi-experimental research, meaning it was not conducted in a laboratory capable of controlling various external factors that might influence changes in the subject's behaviour. The research only consists of the experimental group with male and female subjects and excluded the control due to difficulty getting subjects capable of following the treatment intensely and continuously. The results of data analysis show that group play therapy has a significant effect on improving social skills and abilities for children with autism. This is indicated by the value of z = -2,940, with an increase in the mean of the pre-test and post-test values of 42.9 and 48.5, for 6 weeks. Therefore, there is an increase of 6.3 items from the provision of play therapy.  Research on Social Play Therapy has shown that it can improve social skills and abilities in children with autism due to its play-based approach. This therapy helps children develop social skills such as sharing, turn-taking, and understanding emotions through structured social interactions. Additionally, it provides a supportive environment and trains children to apply the learned skills in their daily lives. With its focus on social interaction and play activities, Social Play Therapy proves to be an effective way to enhance social skills and abilities in children with autism.